2022
DOI: 10.3390/ijerph19137825
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Interventions for the Recovery of Mental Fatigue: A Systematic Review

Abstract: Background: There is evidence that mindfulness-based interventions (MBI) can help one to recover from mental fatigue (MF). Although the strength model of self-control explains the processes underlying MF and the model of mindfulness and de-automatization explains how mindfulness training promotes adaptive self-regulation leading to the recovery of MF, a systematic overview detailing the effects of MBI on the recovery of MF is still lacking. Thus, this systematic review aims to discuss the influences of MBI on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Additionally, acceptance-based intervention techniques are used to raise athletes’ performance levels, demonstrating the value of improving athletes’ flow state experiences in the context of sports [ 57 , 62 , 63 , 64 ]. Furthermore, mindfulness training might enhance athletes’ sporting experiences while also providing psychological benefits [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, acceptance-based intervention techniques are used to raise athletes’ performance levels, demonstrating the value of improving athletes’ flow state experiences in the context of sports [ 57 , 62 , 63 , 64 ]. Furthermore, mindfulness training might enhance athletes’ sporting experiences while also providing psychological benefits [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 14-item “Qualsyst”, with specific criteria (yes = 2, partial = 1, no = 0), was employed to assess the quality of the studies ( Kmet et al, 2004 ) ( Table 3 ). This assessment tool was used in many reviews with similar topics to the present systematic review ( Cao et al, 2022a ; Cao et al, 2022b ; Bravo et al, 2022 ). The quality of each included study was assessed independently by two authors (SC and ZW), and any discrepancies were discussed and resolved via consensus with a third author (SKG).…”
Section: Methodsmentioning
confidence: 99%
“…Not only described as a construct that can be induced via practice but mindfulness has also been conceptualized as a state or as a trait, playing a significant role in fatigue [ 11 14 ]. A plethora of previous research has shown that mindfulness-based interventions (MBIs) could promote psychological health, and alleviate suffering from fatigue [ 15 , 16 ]. Mindfulness has been considered a protective factor against the unprecedented psychological impact caused by the COVID-19 pandemic [ 17 ].…”
Section: Introductionmentioning
confidence: 99%